Gut-kidney-brain axis and daytime sleepiness in Parkinson's disease and chronic kidney disease: an expert narrative review - Yang, Shanshan; Zhu, Canmin; Xiong, Shihong; Wang, Xinyue; Cheng, Ke; Wang, Yuxin; Gong, Na (Frontiers in Aging Neuroscience, 2026)
BackgroundExcessive daytime sleepiness (EDS) is a debilitating comorbidity in over 80% of patients with Parkinson's disease (PD) and chronic kidney disease (CKD). Evidence implicates dysregulation of the gut-kidney-brain axis as a may contribute of EDS pathogenesis, though detailed mechanistic insights remain limited.ObjectiveThis review evaluates the efficacy of interventions targeting the gut-kidney-brain axis in ameliorating EDS among PD and CKD patients, benchmarking outcomes against standard care protocols.MethodsWe systematically queried PubMed, Cochrane Library, Embase, Web of Science, and Scopus for studies published between January 2000 and December 2025. Our search encompassed experimental, observational, and qualitative designs. Two reviewers independently conducted study selection and data extraction. Data synthesis incorporated random-effects models to address methodological heterogeneity.ResultsAnalysis of 68 included studies (n = 15,392 participants) demonstrated that interventions such as specific probiotics significantly reduced Epworth Sleepiness Scale (ESS) scores by 8.2 points (95% CI: 7.1–9.3; I2 = 65%). Furthermore, biomarker-guided personalized strategies (BBPI) yielded a 3.2-fold higher improvement in EDS outcomes (OR = 3.2, 95% CI: 1.9–5.4).ConclusionsTargeting the gut-kidney-brain axis holds substantial promise for managing EDS, supported by moderate-certainty evidence for BBPI-based approaches. However, clinical translation necessitates personalized intervention frameworks and validation through large-scale multicenter trials.